2020
DOI: 10.1111/jog.14577
|View full text |Cite
|
Sign up to set email alerts
|

Second‐trimester acute fatty liver disease of pregnancy: A brief review of the literature and a case report

Abstract: Acute fatty liver disease of pregnancy (AFLP) is a rare life‐threatening medical emergency unique to pregnancy. It is characterized by progressive microvesicular fatty infiltration of maternal hepatocytes, but the exact etiology has yet to be elucidated. AFLP typically manifests in late third trimester or immediately postpartum and seldom during second trimester. Prompt delivery, irrespective of gestational age or severity, is crucial for arresting the insult and permitting recovery. We hereby report a 21‐year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…To date, applying the Swansea criteria reflects the best diagnostic strategy to identify AFLP. However, applying these criteria may delay the diagnosis of AFLP because they seem to be most efficient when the disease is already in an advanced state and life‐threatening complications are occurring 25 . Our data demonstrate that an s‐Flt1 value >31 100 pg/mL may be an additional parameter, if not even a key criterion, besides the Swansea criteria, to focus our attention on the differential diagnosis of AFLP.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…To date, applying the Swansea criteria reflects the best diagnostic strategy to identify AFLP. However, applying these criteria may delay the diagnosis of AFLP because they seem to be most efficient when the disease is already in an advanced state and life‐threatening complications are occurring 25 . Our data demonstrate that an s‐Flt1 value >31 100 pg/mL may be an additional parameter, if not even a key criterion, besides the Swansea criteria, to focus our attention on the differential diagnosis of AFLP.…”
Section: Discussionmentioning
confidence: 89%
“…However, applying these criteria may delay the diagnosis of AFLP because they seem to be most efficient when the disease is already in an advanced state and life-threatening complications are occurring. 25 Our data demonstrate that an s-Flt1 value >31 100 pg/ mL may be an additional parameter, if not even a key criterion, besides the Swansea criteria, to focus our attention on the differential diagnosis of AFLP. We postulate that sFlt-1 levels may herald AFLP before the presence of the Swansea criteria and before the patient is already severely ill.…”
Section: Re Sultsmentioning
confidence: 81%
See 1 more Smart Citation
“…A separate cohort analysis found that 19% of AFLP cases had mutations in the MTP α-subunit responsible for LCHAD deficiency [13]. Most cases of AFLP occur in the third trimester or early postpartum period, but there are case reports as early as the second trimester with the earliest reported case at 18 weeks of gestation [1][2][3][4][5][6]. Clinically, AFLP leads to liver failure but is also associated with renal failure, coagulopathy, hypoglycemia, encephalopathy, and multisystem organ failure [17][18][19]-all of which occurred in the presented case.…”
Section: Discussionmentioning
confidence: 99%
“…e pathophysiology remains unclear, but research has implicated defective mitochondrial fatty acid oxidation as a contributing factor. AFLP typically presents in the third trimester or early postpartum period, but rare cases have been described in the second trimester [1][2][3][4][5][6]. Diagnosis is usually based on the Swansea criteria [7] in conjunction with serologic and biochemical testing although liver biopsy can be performed under certain circumstances.…”
Section: Introductionmentioning
confidence: 99%